Virtual Reality Based Project-Based Learning Model in Online Learning - Sunarti Sunarti; Hie-Ling Ting (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
This research aims at implementation virtual reality (VR) in online learning for the Chinese language of learning. Model learning in this research is project-based learning to support media in VR. The development of VR in online learning used the ADDIE method because this research developed a media and for using it, students have model learning as project-based learning. The target of this research is the effectiveness of using VR in online learning to improve the cognition of students. In this research, VR tested by 20 students to get data of student’s cognitive. The result of this research, VR had effective around 78% compared to without using VR.